2022
DOI: 10.3390/ijerph192013166
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Therapeutic Community Gardening on the Wellbeing, Loneliness, and Life Satisfaction of Individuals with Mental Illness

Abstract: Background: literature on the mental health benefits of therapeutic community gardening is not specific to individuals with mental illness and reports short-term outcomes. The impact of the coronavirus pandemic on intervention effectiveness is also unknown. This study examined the impact of therapeutic community gardening prior to and across the pandemic on the wellbeing of individuals referred for support with their mental illness. Methods: garden members (n = 53; male = 36, female = 17) aged 47.38 ± 13.09 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Continued support and funding is particularly important when considering the involvement of those with mental health issues or who are otherwise vulnerable, as such groups are at most risk of harm if projects are terminated (Ramsden 2021 ). Cessation of funding for therapy groups is particularly detrimental as members usually experience stronger health benefits from gardening than other groups (Soga, Gaston, and Yamaura 2017 ), with those who were able to continue gardening during lockdown having improved mental health outcomes in relation to the rest of the UK population (Wood, Barton, and Wicks 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Continued support and funding is particularly important when considering the involvement of those with mental health issues or who are otherwise vulnerable, as such groups are at most risk of harm if projects are terminated (Ramsden 2021 ). Cessation of funding for therapy groups is particularly detrimental as members usually experience stronger health benefits from gardening than other groups (Soga, Gaston, and Yamaura 2017 ), with those who were able to continue gardening during lockdown having improved mental health outcomes in relation to the rest of the UK population (Wood, Barton, and Wicks 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are also numerous studies and reviews reporting the benefits for STH for individuals with symptoms of mental illness or diagnosed mental illness, aligning with mental health levels 2–4. However, in many cases this data is combined with data from individuals without mental ill-health, or for a range of mental health disorders [ 13 , 16 , 46 ], making it more difficult to isolate the evidence for specific conditions and those who require mental health intervention. Whilst studies focused on individuals at levels 2–4 with mild to severe mental illness have demonstrated positive effects for depression, wellbeing, quality of life and activities of daily living [ 16 , 47 ], many studies fail to incorporate comparison groups or randomisation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This study supports findings of previous research that indicated that nature connection is a significant component of the nature–health relationship. Nature-based interventions are already being used to support various populations, including people who have experienced trauma and people living with mental ill health [ 52 , 53 , 54 ]. To fully understand the role of nature connection for different populations, we recommend that nature-based interventions actively seek to increase nature connection through activities that promote meaningful connection with the natural environment [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%